PERANCANGAN PENERAPAN BALANCED SCORECARD SEBAGAI SUATU SISTEM PENGUKURAN KINERJA PADA INSTITUSI KESEHATAN (Studi Kasus di Puskesmas Gunung Anyar Surabaya) - RAKHMAH HARUM KARISMA (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This research is aimed to show the performance measurement design in health institution using the Balanced Scorecard approach. The object of this research is Gunung Anyar Community health center of Surabaya. This research is a qualitative research with case study approach. Data are collected by a semi- structured interview. Data are analyzed by comparing the implementation of Community helath center Based Management in Gunung Anyar Community health center of Surabaya with relevant theories about Balanced Scorecard to determine the objectives and relevant performance indicators used in the performance measurement design in Gunung Anyar Community health center of Surabayaby using the Balanced Scorecard approach. The results show that the objective of customer perspective is to create satisfaction to the public as the community health centers main customer. The objectives of the financial perspective are to give income retribution ontime, and to implement the budget effectively and efficiently. The objectives of the internal process perspective are to understand the public/ as customer and innovate continuously, to implement effective operational processes, and to do partnering with schools. The objectives of learning and growth perspectives are to meet the needs of human resource skills in a strategic position, to measure the training of human resources, to measure employees satisfaction and to measure the allignment of human resources motivation with the community health center's vision. Keywords: performance measurement design, Balanced Scorecard, health institution